Nationalist Soundscapes: the Sonic Violence of the Far Right - Gillespie, Liam (The British journal of criminology, 2025)
Sound’s ability to impact the body and cross borders places it firmly within the remit of criminological concern. However, although sound continually emerges as a feature of far-right protests and riots—including through music, chants, singing, yelling and drumming—the role it fulfils for the far right has gone untheorized. To address this gap, this article introduces the concept of ‘nationalist soundscapes’, which describes the mechanisms through which far-right nationalists deploy sound to effectuate a politics of power, domination and nationalist superiority. Referencing a selection of events, I argue nationalists weaponize sound in a way that is unique to them, insofar as nationalist soundscapes are deployed to assert ownership over the nation, while simultaneously displacing racialized others through sonic violence.